Забезпечення продовольчої безпеки за еко-соціо-економічною моделлю суспільного розвитку - Кундєєва, Галина Олексіївна (НУБіП України, 2019)
Дисертація на здобуття наукового ступеня доктора економічних наук зі спеціальності 08.00.03 «Економіка та управління національним господарством». Національний університет біоресурсів і природокористування України. Київ, 2019. Дисертацію присвячено розробленню й удосконаленню теоретикометодологічних засад формування та забезпечення продовольчої безпеки країни, створенню інтеграційної моделі забезпечення продовольчої безпеки й обґрунтуванню пропозицій щодо її подальшого застосування. Систематизовано періодизацію генези продовольчої проблеми з позиції розвитку суспільства та запропоновано концептуальний підхід її дослідження. Розроблено еко-соціо-економічну модель суспільного розвитку, яка визначає чітку ієрархію екологічної, соціальної та економічної складових і базується на безпеці кожної із зазначених складових. Запропоновано інтеграційну модель забезпечення продовольчої безпеки, яка орієнтована на забезпеченість громадян продовольством вітчизняного виробництва, самодостатність країни та окремої людини. Обґрунтовано комплексний підхід до формування продовольчої безпеки, що дозволило розширити концепцію продовольчої безпеки такими складовими як безпека харчування та економіка здоров’я. Удосконалено модель здоров’я, яка враховує економічний концепт здоров’я та логічно вбудовується в еко-соціо-економічну модель розвитку суспільства. Запропоновано методичний підхід, який базується на побудові матриці «темп зміни обсягів виробництва / темп зміни обсягу споживання продовольчої групи» та враховує показник «достатність споживання». Удосконалено систему оцінки продовольчої безпеки шляхом виокремлення ознаки «споживання продовольства» й визначено відповідні показники та індикатори. Обґрунтовано необхідність розрахунку безпекового продуктового кошика з позиції мінімізації його вартості задля подолання продовольчої бідності та зміцнення здоров’я людини. Визначено стратегічні пріоритети розвитку сільського господарства та харчової промисловості України (виробництво функціональних харчових продуктів) з позиції економічної доступності безпекового харчування та зміни моделі споживання
Thesis for the degree of Doctor of Economic Sciences, specialty 08.00.03 «Economics and Management of National Economy». National University of Life and Environmental Sciences of Ukraine. Kyiv, 2019. The relevance of the research topic is determined by the effect of the unresolved problems in Ukraine: the necessity to create an effective model for ensuring food security. The purpose of this thesis is to form the theoretical, methodological and methodological principles of ensuring food security of Ukraine based on eco-socio-economic model of social development. The thesis is devoted to the development and improvement of theoretical and methodological principles of formation and provision of food security of the country, to creation of an integration model for food security ensuring, and to substantiation of proposals for its further application. The periodization of the genesis and the peculiarities of the evolution of the food problem from the standpoint of the development of society was formed, and a conceptual approach to the study of the food problem was suggested, which expands the levels of food security by allocating the nano-scales, the safety of the individual. The eco-socio-economic model of the development of society, which has a clear hierarchy of components and is based on the security of each of them, defines interdependencies and interconnections in each subsystem, is suggested, and the general area of combination of the said constituents forms the space that represents the eco-socio-economic safety, which is a prerequisite for ensuring food security. The conceptual framework of the integrated model of food security, which is aimed at provision of citizens with food of domestic production, the self-sufficiency of the country and the individual, is suggested. The application of this model leads to the transition of the domestic economy to a circular type of production, a production in which the waste of one industry become the raw material of another. However, change of production model contributes to change of consumption pattern and forms responsible demand both in the market of resources and in the market of goods and services. Author had created a comprehensive approach to the formation of food security, which focuses not only on production, distribution and exchange, but also on the consumption of food as a vital need to strengthen human health. This allowed the concept of food security to be expanded to include such ingredients as food security and the health economy. The study of the economic essence of human health made it possible to identify health as a resource, a potential and a capital of a society, and to distinguish between the concept of «health promotion» (priority of food security and health economy) and «health care» (the priority of medicine). The bio-socio-economic model of health, which takes into account the economic concept of health and is logically embedded in the eco-socio-economic model of society's development, is substantiated. Consideration of modern determinants of health and their impact on the condition of a person had made it possible to determine the importance of nutrition for the promotion of human health. The undeniable value of health for a person and the possibility of personal strengthening of own health through balanced safe nutrition requires a change in the philosophy of education – the creation of a health-saving concept of human existence and its extension in the modern concept of lifelong learning. The existence of a differentiation of the quantitative and qualitative composition of food on the socio-economic basis led to the need to calculate the security product basket from the point of view of minimizing its cost, and the establishing the existence of an inverse relation between life expectancy and the share of expenditures of households on food products and non-alcoholic beverages led to the creation of an optimal model of consumption (type of food). The system of assessing of food security condition was expanded by identifying the sign of food consumption, the system of indicators was developed in accordance with this feature, and indicators of food security were identified. Indicators that determine the safety of food (balance on the main macronutrients and the caloric content of the food ration on plant and animal origin) and indicators characterizing the «stability» characteristic – unemployment and inflation – are suggested. The obtained results allowed to substantiate the priorities of socioeconomic policy of the state on the principles of social responsibility of all economic actors. The methodical approach that based on the construction of the matrix «the rate of change in production volumes / the rate of change in the consumption of food group» is suggested, and the «consumption adequacy» indicator is considered, which allows to substantiate the state policy regarding the implementation of state subvention to the farmer and consumer, as well as the distribution/restriction of exports, taking into account the food independence of the country. The strategic priorities of the agricultural development of Ukraine are defined: organic production of agricultural products and usage of genetically modified plants along with their deep processing by domestic enterprises on the basis of the dynamic and innovative component of the suggested model of food security, which contributes to solving the problems of employment, increasing rural incomes and increasing the export component of the agrarian sector of the country. Innovative development of the country determines the branches of the fourth and fifth technological structures, which includes biotechnology, the use of the principles of which determines production of food products with improved properties – functional products. The thesis substantiates the necessity for the development of functional food products production from the standpoint of the economic availability of safe food and changing consumption patterns
Keywords: продовольча безпека; безпека харчування; еко-соціоекономічна модель суспільного розвитку; інтеграційна модель забезпечення продовольчої безпеки; функціональні харчові продукти; food security; food safety; eco-socio-economic model of social development; functional food products